Isolation of a novel Rhabdovirus from an insectivorous bat (Pipistrellus kuhlii) in Italy - Davide Lelli; Alice Prosperi; Ana Moreno; Chiara Chiapponi; Anna Maria Gibellini; Paola De Benedictis; Stefania Leopardi; Enrica Sozzi; Antonio Lavazza (Virology Journal, 2018)
Abstract Background Rhabdoviridae is one of the most ecologically diverse families of RNA viruses which can infect a wide range of vertebrates and invertebrates. Bats, among mammals, are pointed to harbor a significantly higher proportion of unknown or emerging viruses with zoonotic potential. Herein, we report the isolation of a novel rhabdovirus, detected in the framework of a virological survey on bats implemented in North Italy. Methods Virus isolation and identification were performed on samples of 635 bats by using cell cultures, negative staining electron microscopy and PCRs for different viruses. NGS was commonly performed on cell culture supernatants showing cytopathic effect or in case of samples resulted positive by at least one of the PCRs included in the diagnostic protocol. Results A rhabdovirus was isolated from different organs of a Pipistrellus kuhlii. Virus identification was obtained by electron microscopy and NGS sequencing. The complete genome size was 11,774 nt comprised 5 genes, encoding the canonical rhabdovirus structural proteins, and an additional transcriptional unit (U1) encoding a hypothetical small protein (157aa) (3’-N-P-M-G-U1-L-5′). The genome organization and phylogenetic analysis suggest that the new virus, named Vaprio virus (VAPV), belongs to the recently established genus Ledantevirus (subgroup B) and it is highly divergent to its closest known relative, Le Dantec virus (LDV) (human, 1965 Senegal). A specific RT-PCR amplifying a 350 bp fragment of the ORF 6 gene, encoding for L protein, was developed and used to test retrospectively a subset of 76 bats coming from the same area and period, revealing two more VAPV positive bats. Conclusions VAPV is a novel isolate of chiropteran rhabdovirus. Genome organization and phylogenetic analyses demonstrated that VAPV should be considered a novel species within the genus Ledantevirus for which viral ecology and disease associations should be investigated.